Aprovechamiento de los tallos de ruibarbo (rheum rhabarbarum) para la elaboración de mermelada endulzada con estevia (stevia rebaudianna) - Tenelanda Toaza, Vilma Elizabeth (2018)
This work of investigation is based on the preparation of rhubarb marmalade, which was sweetened with different stevia percentages in order to take advantage of these crops. Due to lack of farmers, they are not given an adequate use. A bromatological analysis of the rhubarbs stems was carried out before the preparation of the marmalade, in order to know its nutritional composition and make a comparison with the European bibliography; in addition the quality control of the raw material was carried out to know the maturity index, which obtained an average of 2.2 ° Brix. It indicates an optimum state of ripeness to be processed. A multifactorial ANOVA experimental design was performed for the separation of statistical average according to the following factors and levels. Factor A: proportion of sucrose levels; A1: 95% A2: 90% A3: 85% Factor B: stevia concentration levels; B1: 5% B2: 10% B3: 15%. Each factor acted with three levels, then the experiment required 15 treatments in total. Following with the development of this research, different samples of marmalade were made with the purpose of knowing the best formulation which provides a better texture, smell, color, and flavor. From the samples obtained, 2 marmalades were selected (stevia at 10 and 5%), which were those that fulfilled the parameters established by the INEN 419 standard after having carried out the physicochemical, microbiological and organoleptic analyzes. For the sensorial analysis a survey was applied, the results indicated that the marmalade with stevia at 10% had 77% acceptance by the respondents while the marmalade with stevia at 5% had an acceptance of 23%. It was necessary to make the pH , ° Brix and treatable acidity physicochemical analyzes, which achieved average values of 3.12, 64.33 and 0.5 respectively; being within the parameters cited in the NTE INEN 419. The microbiological analysis allowed determining the durability of the marmalade that was superior to 36 days, reporting total absence of E. coli, molds and yeasts. In conclusion, the rhubarb marmalade made up of 90% sugar, and 10%, stevia is an accepted, new and innovative product